Oman's foreign policy between 1970-2008 - Akseki, Emin (Middle East Technical University, 2010)
In this thesis, Oman’s foreign policy between 1970 and 2008 is examined. The main question of this thesis is what the main characteristics of Oman’s foreign policy are. In order to identify the main characteristics of Oman’s foreign policy its determinants are analyzed by looking at its three interacting environments: domestic, regional and international. In other words, the impacts of these three environments on Oman’s foreign policy conceptions, behaviors and decisions are discussed. While examining Oman’s foreign policy, special attention is exerted to its foreign policy towards Iran which is the most influential regional power in the Gulf. It is observed that Oman’s foreign policy towards Iran is the best telling example of how Oman balances the benefits and constraints of the three environments.
Keywords: Politique étrangère – Oman – 1970-2020